John and John IV - unknown:::Creator::::::::::::
John Steinbeck and John Steinbeck IV (uniformed) sitting, probably at the Caravelle Hotel in Saigon the day the elder Steinbeck arrived. John IV was part of Armed Forces TV Detachment Number 3.